2016
DOI: 10.1002/ps.4271
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of chlorantraniliprole on development, reproduction and vitellogenin gene (CsVg) expression in the rice stem borer,Chilo suppressalis

Abstract: Sublethal concentrations of chlorantraniliprole adversely affect the development and reproduction of C. suppressalis. The downregulation of CsVg by chlorantraniliprole might have negative impacts on the fecundity of C. suppressalis. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 28 publications
5
57
0
Order By: Relevance
“…For example, enhanced thermotolerance of Nilaparvata lugens by sublethal concentrations of triazophos was found to be correlated with the upregulation of Hsp70 and arginine kinase genes . Our previous results showed that LC 10 and LC 30 chlorantraniliprole significantly decreased the expression levels of vitellogenin mRNA by 42.52% and 47.84%, respectively, in 12‐h‐old female adults of C. suppressalis , and the fecundity was significantly decreased by 32.18% and 52.94%, respectively . Recently, it was reported that in the green peach aphid M. persicae 4‐ to 31‐fold reduced expression of the FPPS gene was observed in G0 adults when aphid nymphs were treated with 0.01, 0.1, 1, 3 and 10 mg L −1 of precocene .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…For example, enhanced thermotolerance of Nilaparvata lugens by sublethal concentrations of triazophos was found to be correlated with the upregulation of Hsp70 and arginine kinase genes . Our previous results showed that LC 10 and LC 30 chlorantraniliprole significantly decreased the expression levels of vitellogenin mRNA by 42.52% and 47.84%, respectively, in 12‐h‐old female adults of C. suppressalis , and the fecundity was significantly decreased by 32.18% and 52.94%, respectively . Recently, it was reported that in the green peach aphid M. persicae 4‐ to 31‐fold reduced expression of the FPPS gene was observed in G0 adults when aphid nymphs were treated with 0.01, 0.1, 1, 3 and 10 mg L −1 of precocene .…”
Section: Discussionmentioning
confidence: 87%
“…The pupae duration was also significantly prolonged by 2.37 days after exposure to LC 30 . Furthermore, LC 10 and LC 30 significantly decreased the number of eggs laid per female by 32.18% and 52.94%, respectively . We hypothesized that these effects were caused by an effect of the insecticide on the endocrine system regulating development and reproduction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Sublethal effects are effects on the physiology and behavior of an individual exposed to a dose of insecticide without directly causing death . Research has focused on the sublethal effects on development, immunology, and fecundity , . In addition, many behaviors such as learning ability, orientation, foraging, host‐seeking, calling, and brood care may also be affected by a sublethal dose of the insecticide , .…”
Section: Discussionmentioning
confidence: 99%